2022
DOI: 10.5435/jaaos-d-21-00783
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Private Equity Acquisition of Orthopaedic Practices in the United States

Abstract: Background: Private equity acquisition of medical specialty practices has increased in recent years. With the projected increase in the volume of elective, ambulatory orthopaedic procedures, especially in the outpatient setting, private equity firms are increasingly investing in orthopaedic practices. The purpose of this cross-sectional study was to report recent trends and variations in acquisitions of US orthopaedic practices by private equity firms and other institutional investors (venture capital firms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…During this stage, 26 further studies were excluded, leaving 55 studies in the final sample (fig 1). Of these studies, 32 evaluated the impacts of PE ownership on at least one category of health outcomes, costs to patients or payers, costs to operators, or quality, or a combination of these factors,2236373839404142434445464748495051525354555657585960616263646566 (table 1, table 2, and table 3) and 38 reported trends or prevalence of PE among healthcare operators (see supplementary material 3) 2136383940414245495355606163646567686970717273747576777879808182838485868788. Fifteen studies in total reported findings for both impacts and trends 36383940414245495355606163…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During this stage, 26 further studies were excluded, leaving 55 studies in the final sample (fig 1). Of these studies, 32 evaluated the impacts of PE ownership on at least one category of health outcomes, costs to patients or payers, costs to operators, or quality, or a combination of these factors,2236373839404142434445464748495051525354555657585960616263646566 (table 1, table 2, and table 3) and 38 reported trends or prevalence of PE among healthcare operators (see supplementary material 3) 2136383940414245495355606163646567686970717273747576777879808182838485868788. Fifteen studies in total reported findings for both impacts and trends 36383940414245495355606163…”
Section: Resultsmentioning
confidence: 99%
“…Together, the studies evaluating trends in PE prevalence document a noticeable influx of ownership across many healthcare settings over the past 10-15 years, often increasing in yearly deal count over study duration 2165686970717275768182838486. PE acquisitions have been documented across the continental US, but PE ownership was particularly pronounced in the south,21425355697172818789 northeast,7172818889 and, specifically, in Florida39538182838488 and Texas 395360828384.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From 2004 to 2019, 41 practices were acquired by 34 PE firms, with 71% of transactions occurring between 2017 and 2019. 33 The acquisition rate showed a compound annual growth rate of 29.2%, primarily in major metropolitan areas. As of January 2022, there were 14 PE-backed orthopaedic platforms seeking to consolidate musculoskeletal physician practices and approximately $1.8 trillion of PE capital ready to be deployed within health care.…”
Section: Private Equitymentioning
confidence: 99%